2013
DOI: 10.1097/sla.0b013e31826bc313
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Stepped Care Intervention Trial Targeting Posttraumatic Stress Disorder for Surgically Hospitalized Injury Survivors

Abstract: Objective To test the effectiveness of a stepped care intervention model targeting posttraumatic stress disorder (PTSD) symptoms after injury. Background Few investigations have evaluated interventions for injured patients with PTSD and related impairments that can be feasibly implemented in trauma surgical settings. Methods The investigation was a pragmatic effectiveness trial in which 207 acutely injured hospitalized trauma survivors were screened for high PTSD symptom levels and then randomized to a ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
236
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 196 publications
(243 citation statements)
references
References 46 publications
5
236
0
2
Order By: Relevance
“…A similar step-wise care pathway has been shown to improve PTSD symptoms and remission rates in traumatic injury survivors. 37 The incidence of PTSD-related symptom complexes in Psych SOS was substantially higher than would be expected from a random sample of adults in the community. Using DSM-IV criteria, the National Comorbidity Survey Replication suggested that the lifetime prevalence of PTSD in United States adults is about 6.8%.…”
Section: Discussionmentioning
confidence: 95%
“…A similar step-wise care pathway has been shown to improve PTSD symptoms and remission rates in traumatic injury survivors. 37 The incidence of PTSD-related symptom complexes in Psych SOS was substantially higher than would be expected from a random sample of adults in the community. Using DSM-IV criteria, the National Comorbidity Survey Replication suggested that the lifetime prevalence of PTSD in United States adults is about 6.8%.…”
Section: Discussionmentioning
confidence: 95%
“…could be identified before hospital discharge to facilitate receipt of evidencebased treatments with the aim of preventing the development of PTSD (36,37). Additional research is warranted to determine if implementing such interventions for medical-surgical ICU survivors could also prevent post-ICU cognitive impairment.…”
Section: Original Researchmentioning
confidence: 99%
“…Recent research on traumatic injury has focused on psychosocial variables that may impact individuals' recovery, specifically those influencing the onset of depression and posttraumatic symptoms following injury (Bryant et al, 2010;Zatzick et al, 2013;deRoon-Cassini, Mancini, Rusch & Bonanno, 2010;Shih et al, 2012;Powers et al, 2014). One such variable of interest has been perceived injustice, which describes an appraisal reflecting the severity and irreparability of injury-related loss, blame, and unfairness (Sullivan et al, 2008).…”
Section: Impactmentioning
confidence: 99%